2020
DOI: 10.47176/mjiri.34.96
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of regional COVID-19 registry in Hormozgan (RCovidRH), Iran: Rationale and study protocol

Abstract: Background:The rapid outbreak of COVID-19 has resulted in a global pandemic in 2020. Information sources such as disease registries through accessing quality, valid, accurate, and timely data empower researchers and health authorities to study and develop appropriate actions. Our study describes the protocol for implementation of regional COVID-19 registry in Hormozgan province (RCovidRH).Methods: We followed approved phases for the development of RCovidRH to cover the population in Hormozgan. Missioned to dev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 7 publications
(9 reference statements)
0
3
0
Order By: Relevance
“…For instance, a web-based registry specifically designed for COVID-19 aimed to provide a reliable data source for reporting and benchmarking the disease (Kazemi-Arpanahi et al, 2020). The implementation protocol of the regional COVID-19 registry in Hormozgan province emphasised the potential for collaborative studies and data coordination, enabling comprehensive insights into COVID-19 data (Khorrami et al, 2020), and a real-time EHR-based COVID-19 surveillance system demonstrated its effectiveness in monitoring and managing the pandemic (Sheikhtaheri et al, 2022). Our study's customised MDS approach enhances the accuracy and relevance of COVID-19 data in Iran, supporting evidence-based strategies for pandemic control.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, a web-based registry specifically designed for COVID-19 aimed to provide a reliable data source for reporting and benchmarking the disease (Kazemi-Arpanahi et al, 2020). The implementation protocol of the regional COVID-19 registry in Hormozgan province emphasised the potential for collaborative studies and data coordination, enabling comprehensive insights into COVID-19 data (Khorrami et al, 2020), and a real-time EHR-based COVID-19 surveillance system demonstrated its effectiveness in monitoring and managing the pandemic (Sheikhtaheri et al, 2022). Our study's customised MDS approach enhances the accuracy and relevance of COVID-19 data in Iran, supporting evidence-based strategies for pandemic control.…”
Section: Discussionmentioning
confidence: 99%
“…Various studies have highlighted the importance of registries and EHRs in managing COVID-19 data (Kazemi-Arpanahi et al, 2020; Khorrami et al, 2020; Sheikhtaheri et al, 2022; Zarei et al, 2021). For instance, a web-based registry specifically designed for COVID-19 aimed to provide a reliable data source for reporting and benchmarking the disease (Kazemi-Arpanahi et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, a comprehensive database will be helpful to support researchers and clinicians for a better understanding of the disease and proper treatments. 12 As of March 1, 2021, COVID-19 has affected 217 countries and territories with more than 114 million confirmed cases around the world. In Iran, there have been more than 1.6 million total cases and over 60 000 deaths.…”
Section: Discussionmentioning
confidence: 99%